Aetiology and impact of bacterial bloodstream infections in mechanically ventilated COVID-19 patients: A prospective Swedish multicenter cohort study - Isak Olsson; Anna C. Nilsson; Ingrid Didriksson; Attila Frigyesi; Hans Friberg; Anton Reepalu; Martin Spångfors (PLoS ONE, 2026)
Objectives Critically ill COVID-19 patients admitted to the intensive care unit (ICU) are at an increased risk of acquiring bacterial bloodstream infections (BSI). We aimed to describe patient characteristics, risk factors, and the microbiological spectrum in blood cultures and evaluate the impact of ICU-acquired BSI on outcomes in a Nordic setting. Methods A prospective multicenter cohort study was conducted on adult invasively mechanically ventilated (IMV) COVID-19 patients. The primary aim was to identify the proportion of ICU-acquired BSI and its aetiology. Secondary outcomes were duration of IMV, length of stay (LOS), and mortality for individuals with and without BSI, respectively. Logistic regression was used to identify potential predictors of ICU-acquired BSI. Predictors were assessed by calculating an Area Under the Receiver Operating Characteristics (AUROC) curve. Results Of 354 included patients, 17% had an ICU-acquired BSI. Staphylococcus aureus was the most common pathogen. Patients with BSI had a longer duration of IMV (20 days versus 9 days, p < 0.001 ), longer ICU-LOS (24 days versus 11 days, p < 0.001 ), and hospital-LOS (38 days versus 24 days, p < 0.001 ). A BSI was associated with increased mortality; odds ratio (OR) 3.21, 95% CI: 1.61–6.38, p < 0.001 . Adjusted analyses showed that higher BMI; OR 1.06, 95% CI: 1.01–1.11, p = 0.014 , diabetes mellitus with organ complications; OR 2.66, 95% CI: 1.33–5.29, p = 0.005 , and number of symptomatic days before ICU admission; OR 1.04, 95% CI: 1.01–1.07, p = 0.008 , were associated with a BSI. The AUROC was 0.66 (95% CI: 0.58–0.74). Conclusion ICU-acquired BSIs were found in 17% of critically ill COVID-19 patients and were associated with a longer duration of IMV and LOS as well as increased mortality. Staphylococcus aureus was the dominating pathogen . We found several factors associated with ICU-acquired BSIs at ICU admission. However, their ability to predict BSIs was poor.